Tar reduction in downdraft biomass gasifier using a primary method - Machin, Einara Blanco [UNESP]; Pedroso, Daniel Travieso [UNESP]; Proenza, Nestor; Silveira, Jose Luz [UNESP]; Conti, Leonetto; Braga, Lucia Bollini [UNESP]; Machin, Adrian Blanco [UNESP] (Elsevier B.V., 2015)
This work present a novel primary method, for tar reduction in downdraft gasification. The principle of this new technology is to change the fluid dynamic behaviour of the mixture, formed by pyrolysis product and gasification agent in combustion zone; allowing a homogeneous temperature distribution in radial direction in this reaction zone. To achieve the change in the fluid dynamic behaviour of the mixture; the entry of gasification agent to combustion zone is oriented by means of wall nozzles in order to form a swirl flow. This modification in combination with the extension of the reduction zone, will allow, to increases the efficiency of the tar thermal cracking inside the gasifier and the extension of the Boudouard reactions. Consequently, the quantity of tar passing through the combustion zone without cracking and the concentration of tar in the final gas, decrease significantly in relation with the common value obtained for this type of reactor, without affecting significantly the heating value of the producer gas. In this work is presented a new design for 15 kW downdraft gasification reactor, with this technology implemented, the tar content obtained in the experiments never overcome 10 mg/Nm(3), with a lower heating value of 3.97 MJ/Nm(3). (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Biomass; Downdraft gasifier; Gasification; Tar; Swirl flow